Osteoarthritis and Scope of Homeopathy (Homoeopathy for All, 2022)
Osteoarthritis (OA) is by far the most  common form of arthritis and is a  major cause of pain and disability in  older people.1 OA is a disorder characterized  by progressive joint failure in which  all structures of the joint have  undergone pathologic change. The  pathologic sign of OA is hyaline  articular cartilage loss accompanied  by increasing thickness and  sclerosis of the sub chondral bone  plate, outgrowth of osteophytes at  the joint margin, stretching of the  articular capsule, and weakness of  the muscles bridging the joint. There  are numerous pathways that lead to  OA, but the initial step is often joint  injury in the setting of a failure of  protective mechanisms.2
Keywords: Osteoarthritis; disability; injury